2018
DOI: 10.1007/s00345-018-2442-0
|View full text |Cite
|
Sign up to set email alerts
|

Extra-target low-risk prostate cancer: implications for focal high-intensity focused ultrasound of clinically significant prostate cancer

Abstract: Presence or not of an extra-target NCSC in the untreated part of the gland had no impact on RTFS. NCSC lesion can be left untreated and actively monitored. RTFS was 80% at 3 years which support the concept of focal/partial treatment as a treatment option of CSC prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…This method is expected to maintain oncologic outcomes and reduce morbidity rates compared to whole-gland ablation. Most studies of partial-gland HIFU ablation included low- and intermediate-risk patients [ 24 25 26 27 28 29 ], but three recent studies have included high-risk patients as well [ 30 31 32 ]. Baseline PSAs were reported to be lower than eight ng/mL, and most studies used multiparametric MRIs and mapping biopsies for tumor localization.…”
Section: Resultsmentioning
confidence: 99%
“…This method is expected to maintain oncologic outcomes and reduce morbidity rates compared to whole-gland ablation. Most studies of partial-gland HIFU ablation included low- and intermediate-risk patients [ 24 25 26 27 28 29 ], but three recent studies have included high-risk patients as well [ 30 31 32 ]. Baseline PSAs were reported to be lower than eight ng/mL, and most studies used multiparametric MRIs and mapping biopsies for tumor localization.…”
Section: Resultsmentioning
confidence: 99%
“…Nine case series reporting on a total of 1698 patients from 45 to 81 years old were identified (Table 4 ). [ 21 29 ] Most patients were stage T1 or T2 PCa, only 2 studies included patients with stage T3 PCa. [ 25 , 28 ] All of the pre-HIFU mean/median PSA levels were ⩽8 ng/mL.…”
Section: Resultsmentioning
confidence: 99%
“…[ 25 ] TURP was only performed in patients at risk of urinary retention or to prevent early acute urinary retention (AUR). [ 21 , 29 ] The duration of follow-up ranging from 1 to 131 months. Among the studies, systematic biopsy plus targeted biopsy with fusion magnetic resonance imaging (MRI) are reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of presumed low-risk prostate cancer has also evolved from radical to focal therapy and active surveillance due to the visualization of significant lesions in MRI and the predictive value of imaging in the negative part of the gland. Through a single-centre report of patients treated by high-intensity focused ultrasound hemiablation, Dr Villers and his team showed that pathologically insignificant, MRI-negative, extra-target disease did not influence the follow-up course and did not have an impact on the radical treatment-free survival [10]. In active surveillance protocols, the strong negative value of MRI could also avoid the use of confirmatory biopsies in case of negative MRI at entry, and thereby improve patient's heath-related quality of life while avoiding biopsy complications [11].…”
mentioning
confidence: 99%